The value of repetitive transcranial magnetic stimulation combined with amisulpride enhancement olanzapine therapy for resistant treatment-refractory schizophrenia - Yang, Ou; Yu, Liyan; Li, Yang; Zhou, Miaozhen; Huang, Qianying (Frontiers in Psychiatry, 2026)
ObjectiveRepetitive transcranial magnetic stimulation (rTMS) is a widely used enhancement therapy for schizophrenia, but there are few controlled studies on the combination of rTMS and amisulpride enhancement therapy. The aim of this study is to explore the value of rTMS combined with amisulpride enhanced olanzapine therapy for resistant treatment-refractory schizophrenia (TRS) patients.MethodsWe conducted a retrospective analysis based on records of TRS patients who received amisulpride enhanced olanzapine treatment at the Third People’s Hospital of Yongkang City from December 2022 to September 2023. Patients are divided into rTMS group and Non-rTMS group based on whether they receive combined rTMS treatment. We examined the patient’s Positive and Negative Symptom Rating Scale (PANSS) scores, Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) scores, World Health Organization Quality of Life Questionnaire (WHOQOL-BREF), and incidence of adverse events.ResultsAfter treatment, the scores of PANSS in both groups significantly decreased, and the rTMS group was lower than the Non-rTMS group (P<0.05); The scores of RBANS and WHOQOL-BREF in both groups significantly increased (P<0.05); Except for the attention sub item, all other sub scores in the rTMS group were higher than those in the Non-rTMS group (P<0.05); There was no significant difference in the total number of adverse events between the two groups (P>0.05).ConclusionsThe combination of rTMS and amisulpride to enhance olanzapine treatment for TRS may offer potential benefits in symptom management, cognitive function, and quality of life.Core tiprTMS is a widely used treatment method for schizophrenia. This study found that rTMS combined with amisulpride enhanced olanzapine treatment for TRS can significantly improve patients’ symptoms, cognitive function, and quality of life, with tolerability and safety.